Chronic Liver Disease Questionnaire would be a primary screening tool of neuropsychiatric test detecting minimal hepatic encephalopathy of cirrhotic patients. Issue 9 (September 2015) - Hirano, Hirotaka; Saito, Masaya; Yano, Yoshihiko; Momose, Kenji; Yoshida, Masaru; Tanaka, Atsushi; Azuma, Takeshi
<x xml:space="preserve">Abstract</x> Aim The neuropsychiatric test (NP test) is a clinically available modality to confirm minimal hepatic encephalopathy (MHE), but it takes at least 30 min for outpatients to complete. An easier primary screening tool of the NP test would be helpful to predict MHE in routine testing on the public. Methods We performed a prospective cohort study on 59 cirrhotic outpatients at Kobe University Hospital. Laboratory measurements, the NP test and the Chronic Liver Disease Questionnaire (CLDQ) were performed. As an indicator of MHE, cases with and without two abnormal subsets or more in the NP test were compared, and the independent risk factors were statistically examined. Predictive scoring systems of the risk of MHE were established using multivariate logistic regression. Results CLDQ worry (WO) was the best predictive factor of MHE diagnosed by the NP test (P = 0.006). The predictive model using CLDQ WO discriminated well between patients with and without MHE (area under the curve, 0.714; 95% confidence interval, 0.582–0.824). The predictive scores of MHE enable the patient‐specific probability to be easily looked up. Conclusion CLDQ WO was shown to be an independent factor associated with the NP test to diagnose MHE in cirrhotic patients. The easy predictive scoring system of the risk of MHE using CLDQ WO could become a primary screening tool before performing the NP test in a social setting.